Comparison of the use of NBR 8800 and NBR 14762 for the flexural design of steel profiles - Arruda, Jessica Almeida Monteiro; Cortês, Carlos Frederico Macêdo (Seven Editora, 2024)
This article presents the results of the flexural strength of rolled steel profiles with U shape and cold-formed sections of UDCS section (single plate bent U), using the procedures of the Brazilian Standards ABNT NBR 8800:2008, which deals with the design of steel structures and composite steel and concrete structures for buildings,  and ABNT NBR 14762:2010, which addresses the design of steel structures consisting of cold-formed profiles. For the analysis, routines were developed in the Microsoft Excel software, which made it possible to make comparisons regarding the feasibility of using the two types of profiles. The comparisons included groups of profiles of the two types, selected based on similar cross-sectional areas and close moments of inertia, in order to establish more precise parameters for the analysis. The results indicated that, although both profiles meet specific resistance requirements, the normative procedures of the two ABNT standards applied are not directly comparable to each other, which implies the need for different considerations for each type of profile when evaluating its structural feasibility. This difference highlights the importance of a careful analysis in the choice of profiles to be used in structural projects, considering the specificities and limitations of each standard. DOI:https://doi.org/10.56238/sevened2024.026-013